EFECTO DE LA SALINIDAD EN EL CRECIMIENTO SALUDABLE DE ALEVINES DE TILAPIA ROJA (Oreochromis mossambicus x Oreochromis niloticus) - VELIZ CRUZ , ARIEL ALEXANDER (2023)
The research work was conducted at the Aquaculture Facility of the Faculty of Animal and Biological Sciences of the Experimental Campus "La María," owned by the Technical State University of Quevedo, located at Kilometer 7 ½ on the Quevedo – El Empalme road, Los Ríos province. The study assessed the impact of salinity and fungal incidence on the growth of red tilapia fingerlings (Oreochromis mossambicus x Oreochromis niloticus). The experiment lasted for 35 days and took place in 40 L polypropylene tanks. Fingerlings were individually counted, weighed, and randomly distributed among three equal treatments with 25 fingerlings each. T1 had 0 ppm salinity (freshwater), T2 had 15 ppm salinity, and T3 had 30 ppm salinity. Variables measured included weight gain, average weight, absolute growth, specific growth, survival, feed consumption, feed conversion, fungal incidence, and water parameters. At the end, T3 exhibited superior performance (average weight, feed consumption, and fungal incidence), statistically identical to T2. T1 showed a higher feed conversion and elevated water parameter levels. No statistically significant differences were observed in specific growth and survival among treatments. It was concluded that T3 (30 ppm) did not negatively impact productive parameters or water parameters.